PERILAKU MENCUCI TANGAN DAN KEJADIAN KECACINGAN PADA SISWA SEKOLAH DASAR DI KECAMATAN PETANAHAN KABUPATEN KEBUMEN - Siti Muthoharoh; Djauhar Ismail; Muhammad Hakimi (Jurnal Ilmiah Kesehatan Keperawatan, 2015)
Children are the nation’s investment. The future quality of a nation is determined in the children’s current quality. The prevalence of worm infestation in Indonesia is quite high between 60-80% and especially attacks on elementary school children. A long term worm infestation can reduce health that impairs the ability to learn. Risk factors of worm disease include poor environmental sanitation, education level, socio-economic conditions, and health habits such as bowel movement in any places, lack of awareness in hand washing, no footwear as well as geographical conditions.Objective: To know the relationship of hand washing behavior with the incidence of worm on elementary school students in Petanahan Sub-District Kebumen District.The research was observational analytic with a cross sectional design. Sampling was done with a two-level clustering method. The sample size was 213 elementary school students in Grades 3, 4, and 5 that met the inclusion and exclusion criteria. The data was collected using a questionnaire and the results of laboratory tests. Hypothesis testing used chi-square with p <0.05 and 95% Confidence Interval. Data analysis used univariable, bivariable, and multivariable.There was a relationship between worm infestation and hand washing behavior seen from the results that the students who did not wash their hands and were positive with worm infestation were 66 students or 59.46%, while the students that performed hand washing and were negative with worm infestation were 72 students or 70.59%. Statistical test result was significant seen from the p value of 0.0001 and the prevalence ratio of 2.02 (95% CI 1.44 to 2.83).Hand washing behavior on elementary school students of Petanahan District, Kebumen, showed that 52.11% of the students did not wash their hands. There was a relationship between hand washing and worm infestation on elementary school students of Petanahan Sub-District, Kebumen District. Keywords: hand washing behavior, the incidence of worm infestation